Frozen-thawed quality of swamp buffalo spermatozoa cryopreserved with sugar palm juice extender - Rizal, Muhammad; Riyadhi, Muhammad; Yusnizar, Yulnawati (Buffalo Bulletin, 2020)
The objective of this research was to examine the effectivity of sugar palm juice as an alternative extender to cryopreserve buffalo. Moreover, we expected to obtain the best composition of sugar palm juice that can be used widely as an alternative extender for buffalo semen cryopreservation. Semen was collected from swamp buffalo bull using artificial vagina. Fresh, diluted, equilibrated, and frozen-thawed was evaluated for general parameters, i.e spermatozoa progressive motility (M), viability (V) and membrane integrity (MI). Fresh semen that had good quality was diluted up to 1.108 sperm/ml in four different compositions of extenders, i.e lactose extender containing 20% egg yolk as control (C), 74% sugar palm juice + 20% egg yolk + 6% glycerol (SPG6), 73% sugar palm juice + 20% egg yolk + 7% glycerol (SPG7), and 72% sugar palm juice + 20% egg yolk + 8% glycerol (SPG8), respectively. Diluted-semen was equilibrated at 5oC for 4 h. It followed by frozen and stored in liquid nitrogen (-196oC). The results showed that the percentages of M, V, and MI of frozen-thawed spermatozoa in control (C) were 45.83, 59.37, and 57.83%), respectively. These results were significantly (P<0.05) higher than those parameters in SPG7 (30.83, 38.83, and 48.83%), SPG6 (18.33, 38.83, and 40.33%), and SPG8 (18.33, 39.17, and 39.33%). In conclusion, sugar palm juice might not be as ideal as control group in maintaining frozen-thawed swamp buffalo semen quality. But this inform us that in a very remote area where chemical or commercial extenders are not easy to find, sugar palm juice can be an alternative due to the fact that it did not affect the pregnancy rate of AI program. Moreover, the cryoprotectant (glycerol) concentration play important role in order to maintain the spermatozoa post thawed quality.